STANCE AND AUTHORITY OF PEOPLE’S CONSULTATIVE ASSEMBLY DURING REFORMATION ERA - Ahmad Mujib Rohmat; Gunarto Gunarto; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
One of the state-level institution within the governance system of the Republic Of Indonesia is the People’s Consultative Assembly (hereinafter, “MPR RI”, “the MPR’). Prior to the amendment of the Constitution of 1945 (hereinafter, “UUD 1945) during the early period of Reformation (1999-2002), the stance of MPR is considered as the highest statelevel institution in Indonesia empowered with a very broad authority. Based on the idea within the Article 1 sub article (2) of UUD 1945, the understanding as explained in the General Explanatory of UUD 1945 strengthened by the Presidential Decree dated 5 July 1959 as an inseparable part of the UUD 1945, mentioning that the President is responsible to the MPR. Thus, it is to be understood that MPR is the highest institution, or known as the highest state-level institution, so it is common to say that the existence of said institution is to be ruled in the very first part of the UUD 1945.2 The positioning of MPR RI as the highest state-level institution is strengthened by the TAP MPR Nomor IV/MPR/1973 regarding the Stance and Relation amongst the Highest State-Level Institutions with/or Interrelation of Highest State-Level Institution.3 The amendment of the UUD 1945 in the early reformation era, 1992-2002 had changed the very basic ground of the governance system of Indonesia, including the stance of MPR. Through said changes, the MPR is no longer placed as the highest state-level institution to execute the sovereignty of the nation [Article 1 sub article (2)]. It means that the MPR is no longer the source/institution of the state’s highest authority that distributes the authority to the other state-level instituions.4 In regard to this notion, Jimly Asshiddiqqie establishes that subsequent to the amendment of the UUD 1945, “Highest State-Level” institution is no longer acknowledged. In accordance with the doctrine of separation of power within the principle of checks and balances amongst the branches of state’s authority, MPR has the equal position to the other state-level institution.5 The amendment of constitution is to be seen as the changes of fundamental aspects of governance system, from the vertical-hierarchy system with the principal of supremacy of MPR down to the horizontal-functional principal that balances and checks amongst the state institution.6 The Chief of Central Representative Body (DPP) Golkar Party, Aburizal Bakrie suggested that Golkar desired to have a platform that can accommodate the people of Indonesia for the next 25, 50 and up to 100 years. He suggested, due to the absent of GBHN hence the national policy-making process is lied upon the Presidential domain of work and can only reach maximum 5 years of service period. Even if said President is to be re-elected for the next five years of service period, the maximum range will only be extended to 10 years. This 10 years range is deemed too short to set out the national development plan. Hence, it is highly needed to have a national program for long term period for any Ruling President.7 From said explanation regarding the platform, it can be understood that Golkar Party wanted to have the GBHN re-implemented. In the end of service period of MPR members of 2009-2014 period, the MPR set out a General Assembly (GA) Meeting in the end of September 2014 in Jakarta. The results of the Ad Hoc II BP MPR that was validated by the GA are the seven recommendations of the next period of MPR. Said recommendations are the changes of UUD 1945 to strengthen the role of MPR as the institution in amending, establish and to elucidate the UUD 1945.8 In full, the recommendation of the Research Team of Governance System of Indonesia – MPR is “to strengthen the MPR as the state’s institution which has the highest authority in amending, establishing, elucidating the UUD and to give a directive of national policy to the other state’s institutions.”9